2015
DOI: 10.4103/0971-6203.170786
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dose rate on accuracy of intensity modulated radiation therapy plan delivery using the pretreatment portal dosimetry quality assurance and setting up the workflow at hospital levels

Abstract: The aim of this study was to examine the impact of dose rate on accuracy of intensity modulated radiation therapy (IMRT) plan delivery by comparing the gamma agreement between the calculated and measured portal doses by pretreatment quality assurance (QA) using electronic portal imaging device dosimetry and creating a workflow for the pretreatment IMRT QA at hospital levels. As the improvement in gamma agreement leads to increase in the quality of IMRT treatment delivery, gamma evaluation was carried out for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Lowering the dose rate helps to improve the gamma pass rate. This is in agreement with the work done by Kaviarasu et al…”
Section: Resultsmentioning
confidence: 66%
“…Lowering the dose rate helps to improve the gamma pass rate. This is in agreement with the work done by Kaviarasu et al…”
Section: Resultsmentioning
confidence: 66%
“…Because this radiotherapy modality damages healthy tissues less, it is mainly indicated for treatment next to structures and/or vital organs, such as in patients with head and neck tumors. 46,47 Some studies reached consensus 5,14,16,18 on the risk of the radiotherapy dose, values of 50 to 60 Gy were predominant. In those situations, the use of HBO would be indicated, because this treatment improves bone repair and assists in the osseointegration process 24 by stimulating the irradiated tissues and significantly increasing the oxygen content areas prone to osteoradionecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Kaviarasu et al examined the impacts of dose rate on accuracy of intensity modulated radiation therapy (IMRT) plan delivery by comparing the gamma agreement between the calculated and measured portal doses by pretreatment quality assurance (QA) using electronic portal imaging device dosimetry (15) . They showed that lower dose rate (300 MU/ min) decreased gamma values compared to the increased dose rate (500 MU/min).…”
Section: Gul and Inanmentioning
confidence: 99%